2004
DOI: 10.1016/j.dsr.2003.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of transparent exopolymer particles (TEP) in the northeast Atlantic Ocean and their potential significance for aggregation processes

Abstract: The abundance of transparent exopolymer particles (TEP) was determined in the northeast Atlantic Ocean (40-55 N, B20 W) during several cruises from June to November 1996. An accumulation of TEP in the water column was observed at bloom and post-bloom sites along a 20 W transect in June/July (maximum concentration: 124 mg Gum Xanthan equivalents (Xeq.) l À1 ), but concentrations were uniformly low (mean concentration: 28.5710.2 mg Xeq. l À1 ) during autumn at the BIOTRANS site (47 N, 20 W). TEP concentrations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
112
2
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(129 citation statements)
references
References 34 publications
(53 reference statements)
10
112
2
5
Order By: Relevance
“…4a, Table 2). Our measured TEP concentrations correspond 470 with values and trends reported from other marine environments (Engel, 2004 LDB a significant negative correlation of TEP with DIP was also observed (Fig. 4b, p<0.001), 485…”
Section: Diazotrophic Bloom Demise In the Ld Stations 348supporting
confidence: 66%
See 1 more Smart Citation
“…4a, Table 2). Our measured TEP concentrations correspond 470 with values and trends reported from other marine environments (Engel, 2004 LDB a significant negative correlation of TEP with DIP was also observed (Fig. 4b, p<0.001), 485…”
Section: Diazotrophic Bloom Demise In the Ld Stations 348supporting
confidence: 66%
“…TEP concentrations (µg GX 200 equivalents L -1 ) were measured according to Passow and Alldredge (1995). To estimate the role of 201 TEP in C cycling, the total amount of TEP-C was calculated using the TEP concentrations at each 202 depth, and the conversion of GX equivalents to carbon applying the revised factor of 0.63 based on 203 empirical experiments from both natural samples from different oceanic areas and phytoplankton 204 cultures (Engel, 2004). 205…”
Section: Transparent Exopolymeric Particles (Tep) 194mentioning
confidence: 99%
“…(12)), which suggests that the choice of the coagulation model may become important, and aggregate-dust stickiness and dust particle release by the decay of organic material control the free dust concentration profile. Since the model results are not sensitive to the stickiness parameter value, we did not include any mixed layer TEP dynamics (Prieto et al, 2002;Engel, 2004). Aggregate-dust stickiness in the deep ocean appears to be more important, at least in our model, but according to our knowledge there is not suitable information regarding these processes.…”
Section: Discussionmentioning
confidence: 99%
“…Exudation by phytoplankton plays a significant role in the formation of TEP (Passow, 2002b;Gärdes et al, 2011). Numerous studies have shown that exopolymer particles accumulate in phytoplankton cultures (Passow, 2002b;Claquin et al, 2008;Fukao et al, 2010) and during blooms (Passow et al, 1994;Engel et al, 2002;Engel, 2004;Harlay et al, 2009) (Figs 3,5). Generally, TEP are not exuded directly by phytoplankton cells; they form abiotically from precursors released by cells.…”
Section: 4mentioning
confidence: 99%